PERFORMANCE OF ISLAMIC BASED SCHOOL TEACHERS IN TEMBALANG SUB-DISTRICT, SEMARANG CITY AFFECTED BY INTELLECTUAL INTELLIGENCE AND SPIRITUAL INTELLIGENCE - Anis Turmudhi (Universitas Semarang, 2019)
Abstract This Research has a background from several teacher education qualifications that are not yet in accordance with the teacher's education qualifications that should be a teacher. The focus of the problem in this research is the influence of intellectual intelligence and spiritual intelligence on teacher performance partially and simultaneously. So the purpose of this research is to analyze and explain the influence of two intelligence variables partially and simultaneously on the performance of Islamic based elementary school teachers in Tembalang District, Semarang City.This research method uses quantitative analysis. The number of samples is 87 people, so the data collection uses total sampling technique. Data collection techniques with questionnaires, and data were tested using multiple regression analysis.The results of the study were intellectual intelligence that had a positive but not significant effect on teacher performance. Spiritual intelligence has a positive and significant effect on teacher performance. As well as intellectual intelligence and spiritual intelligence together have a positive and significant effect on the performance of Islamic based elementary school teachers in Tembalang District, Semarang City. The limitations in this study are that there is little time and minimal funding. Keywords: intellectual intelligence, spiritual intelligence, and teacher performance